Mapping our way to coherence, alignment and responsiveness - Bester, Marianne (South African Journal of Higher Education, 2016)
Transformation of higher education in South Africa has resulted in an ongoing need to reflect critically on the relevance and responsiveness of higher education curricula. If we argue that higher education curricula is about complex learning, then it is important to ask: How do we as higher education lecturers create curricula that would provide students with meaningful learning experiences as they progress along their higher education journey? Knight (2001, 370) argues that curricula that sustain complex learning ought to be ‘coherent and progressive’, emphasising that the key elements of a curriculum such as subject content, intended learning outcomes, teaching, learning and assessment strategies and methods should be closely aligned. We shall argue in this paper that curriculum mapping, both as a process and a tool will encourage higher education lecturers to consider these key issues when designing curricula: • What do we teach? • Why do we teach what we teach? • What do our students learn? • How do our students learn? • How do we assess what students have learned? • How well should students perform in these assessment tasks to show that they have achieved the intended learning outcomes? These questions relate to the three levels of a curriculum, namely the intended (planned), the taught (created) and the learned (experienced).